2023
DOI: 10.1002/cncr.34726
|View full text |Cite
|
Sign up to set email alerts
|

Rate of COVID‐19 vaccination among patients with cancer who tested positive for severe acute respiratory syndrome‐coronavirus 2: Analysis of the American Society of Clinical Oncology Registry

Abstract: Background:The availability of safe and effective COVID-19 vaccines has enabled protections against serious COVID-19 outcomes, which are particularly important for patients with cancer. The American Society of Clinical Oncology Registry enabled the study of COVID-19 vaccine uptake in patients with cancer who were positive for severe acute respiratory syndrome-coronavirus 2.Methods: Medical oncology practices entered data on patients who were in cancer treatment. The cohort included patients who had severe acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Most patients in our cohort were fully or partially vaccinated and only 16% of patients were not vaccinated. COVID-19 vaccine uptake in our study was comparable to a previous study that used American Society of Clinical Oncology Registry data (33), revealing that younger age, diagnosis of a metastatic tumor or non-B-cell hematologic malignancies, and co-morbidities were associated with lower vaccine uptake. In our study, non-vaccinated status was higher in patients with prior COVID-19 infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Most patients in our cohort were fully or partially vaccinated and only 16% of patients were not vaccinated. COVID-19 vaccine uptake in our study was comparable to a previous study that used American Society of Clinical Oncology Registry data (33), revealing that younger age, diagnosis of a metastatic tumor or non-B-cell hematologic malignancies, and co-morbidities were associated with lower vaccine uptake. In our study, non-vaccinated status was higher in patients with prior COVID-19 infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…In the US, surveys performed by the Centers for Disease Control and Prevention (CDC) show lower bivalent booster adoption rates in younger adults, people living in rural areas, Americans without health insurance, and in Black and Hispanic Americans. Studies analyzing cancer patients showed that counterintuitively, people with more aggressive cancers were less likely to be vaccinated and that patients with comorbid diseases in addition to cancer were also less likely to be vaccinated [22] , even though their comorbid cardiovascular, gastrointestinal, or autoimmune diseases likely placed them at risk for severe COVID-19 disease. This highlights the importance of utilizing antibody testing in conjunction with consideration for social determinants of health, including level of education and other socioeconomic factors, to identify individuals at highest risk of vaccine hesitancy, risk of vaccine non-response, and complications from COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of studies about COVID-19 vaccination in patients with diabetes mellitus, vaccine hesitation rates of about 30% were reported, with a lack of information mentioned as a significant reason for this finding [7]. Promising uptake in vaccination has however been reported in populations with cancer, with age, multiple comorbidities, and level of education identified as factors driving it [8].…”
Section: Introductionmentioning
confidence: 99%